(untitled) (Innovate Conferences, 2025)
The concept of "business city" or business cities has emerged as one of the key trends in modern infrastructure development. A business city represents a comprehensive integration of office, commercial, residential, hotel, and other facilities that create a favorable environment for entrepreneurial activity. In the context of globalization and increasing competition, the establishment of business cities is becoming a crucial factor in stimulating regional economic activity and attracting investments.